THE PRESSURE OF DEMOGRAPHIC CHANGES ON NATURAL RESOURCES - Nurmatova Soxiba Isomiddinovna (International Scientific and Current Research Conferences, 2025)
Demographic change reshapes the scale, composition, and geography of resource demand. Population growth, urbanization, declining household size, internal migration, and dietary transitions together intensify pressures on land, water, energy, and biodiversity, even as technology and policy attempt to decouple welfare from material throughput. This article synthesizes economic, demographic, and environmental literatures to explain how demographic drivers translate into resource use, emphasizing the roles of consumption structure, spatial sorting, and governance capacity. Using a narrative, theory-informed review anchored in impact-decomposition identities (I=PAT and Kaya) and the water–energy–food nexus, we show that the resource footprint of societies is determined less by headcount alone than by age structure, urban form, household composition, and income-mediated preferences. The analysis concludes that managing resource pressure requires integrating demographic foresight with adaptive governance that protects ecological limits while enabling equitable development.